2020
DOI: 10.3390/ijms21041229
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Protects Photosystem II by Alleviating Photoinhibition in Arabidopsis thaliana under High Light

Abstract: Salicylic acid (SA) is considered to play an important role in plant responses to environmental stresses. However, the detailed protective mechanisms in photosynthesis are still unclear. We therefore explored the protective roles of SA in photosystem II (PSII) in Arabidopsis thaliana under high light. The results demonstrated that 3 h of high light exposure resulted in a decline in photochemical efficiency and the dissipation of excess excitation energy. However, SA application significantly improved the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…It is associated with the electron transport and is one of the four multisubunit complex of chloroplast thylakoid membranes. The PS II 32- kDa and 47-kDa membrane proteins, designated as D1 and CP47 are encoded by the plastid psbA and psbB genes, respectively 35 , 36 . Plants initiate mechanisms to withstand salt stress conditions, and there might be ethylene involvement in reducing salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with the electron transport and is one of the four multisubunit complex of chloroplast thylakoid membranes. The PS II 32- kDa and 47-kDa membrane proteins, designated as D1 and CP47 are encoded by the plastid psbA and psbB genes, respectively 35 , 36 . Plants initiate mechanisms to withstand salt stress conditions, and there might be ethylene involvement in reducing salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…The D1 protein constitutes the core of the PS II reaction center [ 2 , 5 ], and many studies have indicated that the PS II center in chloroplasts is the part that is the most easily damaged by environmental stresses [ 9 ]. Therefore, to identify the role of MeJA in the PS II system and in the maintenance of efficient turnover of D1 protein, the abundance of the PS II reaction center D1 protein in wheat leaves was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The adaptive reaction of plants to oxidative stress consists in the rise of the activity of antioxidants enzymes [ 8 , 9 , 10 ]. Remarkably, several studies reported the association between antioxidant activity, heat tolerance, and plant hormones [ 3 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the oxidative scavenging effect also is extended to other stresses, which include excess light, heat, and dark chilling. Furthermore, it leads to decrease photosystem II abundance, photochemical efficiency, chlorophyll content, and changed plant morphology (Nievola et al, 2017;Chen et al, 2020;Gao et al, 2020). Wu et al explained the ameliorative effect of the anionic CeO NPs in the A. thaliana plant against abiotic stress, including excess heat, light, dark, and chilling (Wu et al, 2017b).…”
Section: Cerium Nps (Ceo Nps)mentioning
confidence: 99%